Reflexivities and Knowledge Production in Migration Studies: Pitfalls and Alternatives (IMISCOE Research Series; Social Sciences; Social Sciences (R0), 2026)
This open access book brings together cutting-edge work on reflexive approaches within migration studies and emphasizes the boundedness and political character of knowledge production. Beyond presenting a state-of-the-art of the problematic aspects of knowledge production in migration studies, this volume is innovative insofar as the contributions all formulate alternatives. They should lead to transform knowledge production in relation to migration and therefore contribute to alter our ways to do research and tackle established power relations. By discussing a diverse range of topical subjects – among others, epistemology, power, ethnocentrism, racism, decoloniality, gender and methodology – this volume is a great resource to students, to junior and senior academics in migration studies and social sciences more general as well as to policy-makers in European countries.